Influence of casting mode on the structure and physical characteristics of sacrificial zinc anodes - A. G. Anisovich; I. N. Rumjantseva; E. F. Baranovsky; G. P. Korotkin (Литьë и металлургия, 2001)
The article presents the results of investigation of structure, specific weight, electrical conduction and thermoelectromotive force of zinc strands manufactured by chill casting and by continuous casting, as well as by rolling of ingots and thin block casting^. Solubility of zinc anodes produced in this way in electroplating baths is studied.